2013
DOI: 10.3109/13651501.2013.793359
|View full text |Cite
|
Sign up to set email alerts
|

One-year outcomes of unipolar depression patients with manic or hypomanic switch during acute antidepressant treatment

Abstract: The subjects were considered to have a bipolar nature according to the prevalence rate of bipolar conversion over a one-year period. Longer follow-up studies appear warranted determine the diagnostic issues of antidepressant-induced switch in unipolar depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…The finding that younger age of depression first onset is a useful predictor is consistent with the recent meta‐analysis while this is the first report suggesting that current age, job status, and early response to antidepressant treatment could be other predictors. Our findings suggest that hypomanic and/or manic switch among patients with unipolar major depression during acute‐phase antidepressants treatment is less frequent than that suggested by previous findings (18.9%) . In addition, patients’ current age as well as age at onset of first episode and job status are potential relevant clinical factors and we should also pay attention to early treatment response.…”
mentioning
confidence: 43%
See 1 more Smart Citation
“…The finding that younger age of depression first onset is a useful predictor is consistent with the recent meta‐analysis while this is the first report suggesting that current age, job status, and early response to antidepressant treatment could be other predictors. Our findings suggest that hypomanic and/or manic switch among patients with unipolar major depression during acute‐phase antidepressants treatment is less frequent than that suggested by previous findings (18.9%) . In addition, patients’ current age as well as age at onset of first episode and job status are potential relevant clinical factors and we should also pay attention to early treatment response.…”
mentioning
confidence: 43%
“…Most patients with bipolar disorder have depressive onset polarity. There are, however, very few studies investigating predictors of hypomanic and/or manic change for patients with major depression in Japan . We preliminarily explored predictors of hypomanic and/or manic switch during acute‐phase antidepressants treatment by using the data of the SUN☺D trial, which is a multicenter randomized controlled clinical trial.…”
mentioning
confidence: 99%
“…Compared to conversion risks in studies with prospective assessments, conversions risks were higher in the five studies with retrospective assessment only: 10.1% within 1 year of follow‐up in the only study using survival analysis (Table ) and, in studies not using survival analysis (Table ), 32.8% during a mean of 18.5 years of follow‐up, 18.9% in 1 year, 30.2% during a median follow‐up period of 189 days, and 35.5% during a mean follow‐up period of 8.8 years …”
Section: Discussionmentioning
confidence: 91%
“…, 32.8% during a mean of 18.5 years of followup,33 18.9% in 1 year,36 30.2% during a median follow-up period of 189 days, 14 and 35.5% during a mean follow-up period of 8.8 years. 25 The large study (N=2146) by Tondo et al using historical data based on clinical assessments of patients in a Mood Disorder Center between 1977 and 2013 37 found that 29.9% of the patients initially…”
mentioning
confidence: 94%
“…We identified from the database any cases demonstrating a direct transition (without any symptom‐free interval) from a depressive into a manic or hypomanic episode following the prescription of an ADM. Cases were classified as ATEM+ if: (i) the episode met DSM‐IV criteria for a full syndromal manic or hypomanic episode (defined according to the DIGS); (ii) the onset of the (hypo)mania occurred within 90 days of commencing treatment with an ADM for a depressive episode and the duration of the ATEM also met DSM‐IV criteria; and (iii) the ADM was prescribed as a monotherapy or was coprescribed with a recognised mood stabilizer (as defined by Wada et al ).…”
Section: Methodsmentioning
confidence: 99%